2020
DOI: 10.1093/tropej/fmaa076
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Phone-Based Support on Exclusive Breastfeeding and Infant Growth in Nigeria: A Randomized Controlled Trial

Abstract: Background This study examined whether mobile phone-based support improve the rates, duration of exclusive breastfeeding (EBF) as well as infant growth patterns in Nigeria. Methods A 6-month prospective randomized controlled trial with 75 participants assigned to receive ‘usual care’ or ‘mobile phone-based support in addition to usual care’ EBF rates and duration as well as anthropometric measurements of infants before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…It has been reported that the intervention of mobile phone assisted breastfeeding counseling in Nigeria is associated with the weight of babies in only the sixth month of anthropometric characteristics 19 . In another study, it was reported that the height and weight after breastfeeding education intervention were higher in the intervention group in the second postpartum month, while in the 12th month, when the difference decreased in 6 months, there was almost no difference 20 . The results of the literature differ in themselves and with the findings of the research.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that the intervention of mobile phone assisted breastfeeding counseling in Nigeria is associated with the weight of babies in only the sixth month of anthropometric characteristics 19 . In another study, it was reported that the height and weight after breastfeeding education intervention were higher in the intervention group in the second postpartum month, while in the 12th month, when the difference decreased in 6 months, there was almost no difference 20 . The results of the literature differ in themselves and with the findings of the research.…”
Section: Discussionmentioning
confidence: 89%
“…It was developed by Bandura 20 and Tokat et al 21 and consists of a total of 14 questions evaluating breastfeeding self-sufficiency in Turkish validity and reliability breastfeeding. The scale is a 5-point Likert scale and the minimum score from the scale is 14 and the maximum score is 70.…”
Section: Breastfeeding Self-proficiency Scaleshort Formmentioning
confidence: 99%
“…Houve diferença na média de 0,6 meses (IC: 95%; 0,22-1,42) na duração do AME entre os GI e GC (t= 1,45; p= 0,149). (20) No Brasil, um ECR testou uma intervenção educativa por telefone, centrada na autoeficácia em amamentar, e evidenciou ser eficaz para elevar a autoeficácia materna e a duração do AM aos dois meses (p= 0,35). (9) No contexto do Nordeste brasileiro, ensaio clínico que desenvolveu intervenção participativa online para promover e apoiar o AME apontou que as frequências de AME foram maiores no GI em comparação com o GC, em todos os meses de acompanhamento (1 mês p= 0,031; aos 2, 3, 4, 5 e 6 meses p = 0,000).…”
Section: Discussionunclassified
“…Mobile health increased hospital delivery from 44% to 80.1% in Kenya [ 16 ] and showed improvement in tracking systems that improved maternal and child health in Rwanda [ 17 , 18 ]. The application of mobile phone text and video services improved maternal and child health in Uganda [ 19 ], Cape Town [ 20 ], South Africa [ 21 , 22 ], Nigeria [ 23 ], Pakistan [ 24 ], and Ethiopia [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%